DETERMINANTS OF THE IMPLEMENTATION LEVEL OF ELECTRONIC HUMAN RESOURCES MANAGEMENT (E-HRM) IN JORDANIAN SHAREHOLDING COMPANIES - Al-Dmour, Rand H.; Shannak, Rifat O. (European Scientific Journal, ESJ, 2012)
The main objectives of this study were: identifying the key determinants of the implementation level of E-HRM applications in Jordanian shareholdings companies. In order to achieve the research objectives, a conceptual framework was developed. The conceptual framework tied together the major factors proposed to determine the company.s level of implementation of E-HRM applications. A survey research was carried out where the sample was collected from Amman Stock exchange Market database. The target population under investigation was all the shareholding companies. The random sample has covered only 50% of the total number of these companies which were (257) companies in total. The survey was targeted to HR managers in shareholding companies. The data was collected using a self-administered structured questionnaire. The main findings of study were: the implementation level of E-HRM is considered to be moderate. About 60% of the variations of the implementation level of E-HRM can be explained by internal factors whereas about 14% of variations can be explained by external factors. The adopters and non- adopters of E-HRM were found to be different in terms of their internal and external environmental characteristics in many ways. At the end, the research has come up with several recommendations that were suggested for policy.makers in shareholdings companies in order to improve their level of implementation of E-HRM application.